Assessment of bacterial profiles in aged, home-made Sichuan paocai brine with varying titratable acidity by PacBio SMRT sequencing technology. (August 2017) - Cao, Jialu; Yang, Jixia; Hou, Qiangchuan; Xu, Haiyan; Zheng, Yi; Zhang, Heping; Zhang, Liebing
Abstract: Sichuan paocai, a traditional Chinese fermented vegetable, is rife with lactic acid bacteria (LAB). However, the precise bacterial profiles of home-made Sichuan paocai brine (HSPB) remain unclear. In this study, the bacterial compositions of 38 aged HSPB samples with varying titratable acidity (TA) were determined by SMRT sequencing of the full-length 16S rRNA gene. The lactic and acetic acids of HSPBs were also measured to determine any relevance with the bacterial profiles. The SMRT sequencing results reveal that the HSPB bacterial communities were comprised of numerous phylogenetic taxa, including 35 phyla, 371 genera, and 593 species; the bacterial diversity decreased as HSPB acidity increased. Lactobacillus acetotolerans, which was positively correlated to HSPB acidity, was the most dominant species followed by Lactobacillus brevis, which was positively related to acetic acid in the samples. A few opportunistic pathogens (e.g. Serratia marcescens and Stenotrophomonas maltophilia ) were also detected. Sample groups with lower acidity had higher bacterial diversity and more Lactobacillus species with relative abundance >1% and opportunistics than higher-acidity samples. The results presented here report the comprehensive bacterial profiles of home-made Sichuan paocai for the first time via SMRT sequencing technology and the correlation between TA and bacterial compositions. It is necessary to further investigate the opportunistics detected in this work as they relate to the safety and quality of paocai. Highlights: Bacterial profiles in Sichuan paocai were revealed by SMRT sequencing technology. Lactobacillus acetotolerans was the most dominant species. New species and some opportunistic pathogens were also detected. Bacterial diversity decreased as the acidity of home-made Sichuan paocai increased. Low acidity group had more Lactobacilli and opportunistic pathogens.